Self-Compassion and Subjective Well-Being Working Mothers During The COVID-19 Pandemic - Aghniacakti, Ainindita; Zuliani, Siti; Zduroikhan, Taufiq (Rifa'Institute, 2021)
Due to the COVID-19, most workers are experiencing Work From Home (WFH). Changes in the work environment and greater responsibilities experienced by working mothers can have psychological impact and reduce their level of subjective well-being. This study aims to determine the relationship between self-compassion and subjective well-being in working mothers. This research uses quantitative correlational with 48 working mothers in RW 01 Jatimulyo Village, Malang City. The measuring instrument used was self-compassion scale (16 valid items ?=0.680), Positive and Negative Affect Scales (13 valid items ?=0.771), and Satisfaction with Life Scale (5 valid items ?=0.779). The results of data analysis using simple regression analysis showed p = 0.014 (p < 0.005). The results show that the hypothesis is accepted. There was a positive relationship between self-compassion and psychological well-being toward working mothers in RW 01, Jatimulyo Village, Malang City, with 12.4% as its effective contribution